2007
DOI: 10.1002/bit.21392
|View full text |Cite
|
Sign up to set email alerts
|

Production of synthetically created phospholipase A2 variants with industrial impact

Abstract: Phospholipases A(2) (PLA(2)) play an important role for the production of lysophospholipids. Presently they are mainly obtained from porcine or bovine pancreas but these mammalian sources are not accepted in several fields of application. To make accessible a non-mammalian PLA(2) to industrial application, synthetic genes encoding PLA(2) from honey bee (Apis mellifera) with modified N-termini were constructed and expressed in Escherichia coli. While expression of the gene with an N-terminal leader sequence to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…In our studies on atPLA 2 , bvPLA 2 and ppPLA 2 we noticed significantly different stabilities despite their common fold [26]. In contrast to bvPLA 2 [5,27], which displayed typical cooperative unfolding transitions, ppPLA 2 showed much broader transitions at higher denaturant concentrations or temperatures. The present study aims to reconcile these contradictory stability data of ppPLA 2 .…”
Section: Introductioncontrasting
confidence: 52%
See 1 more Smart Citation
“…In our studies on atPLA 2 , bvPLA 2 and ppPLA 2 we noticed significantly different stabilities despite their common fold [26]. In contrast to bvPLA 2 [5,27], which displayed typical cooperative unfolding transitions, ppPLA 2 showed much broader transitions at higher denaturant concentrations or temperatures. The present study aims to reconcile these contradictory stability data of ppPLA 2 .…”
Section: Introductioncontrasting
confidence: 52%
“…In our previous studies of the related bee venom enzyme, bvPLA 2 , we observed, however more consistent parameters (31.4 kJ mol −1 and 3.25 M, respectively) [27]. In order to clarify this apparent inconsistency, we restudied GdnHCl induced unfolding of ppPLA 2 by far-UV CD and intrinsic fluorescence measurements.…”
Section: Gdnhcl and Gdnhscn Induced Unfolding Of Ppplamentioning
confidence: 62%
“…[56][57][58] For example, there is no change in the optical rotary dispersion (ORD) spectrum of honeybee PLA 2 from 10 to 90 1C 59 and no change in the ORD or CD spectra of porcine PLA 2 upon increasing the urea concentration from 0 to 8 M. 60 Common among the members of the PLA 2 superfamily of enzymes 61 are a large number of disulfide bonds (5)(6)(7)(8) for their relatively small sizes (13-18 kDa). [62][63][64] The high density of disulfide bonding is the foundation of their rigid structures and their stability to proteolysis and resistance to denaturation. 57,58 Nanoelectrospray mass spectra of phospholipase A 2 from cobra venom (c-PLA 2 ; 7 disulfide bonds) in aqueous 200 mM ammonium acetate (pH 7.2) solutions containing 0 to 1.5% m-NBA are shown in Fig.…”
Section: Highly Disulfide-bonded Phospholipase Amentioning
confidence: 99%
“…Previous studies have been mainly focused on expression and characterization of eukaryotic secretory PLA 2 s. While eukaryotic PLA 2 s have been successfully expressed in yeast [4][5][6][7] and fungus [8], inclusion bodies were formed when expressed in Escherichia coli due to the presence of five to eight disulfide bonds [9,10]. Nevertheless, it would be desirable to establish an E. coli-based PLA 2 expression system because eukaryotic systems are generally considered as time consuming and uneconomic in comparison to prokaryotic systems.…”
Section: Introductionmentioning
confidence: 99%